The Effect of Career-Related Course on the Career Decision Making Self-efficacy of Senior University Students - Özlem Ulaş Kılıç (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The aim of this study is to evaluate the effect of an “Interviewing Skills in Career Counseling” course on the level of career decision-making self-efficacy of senior university students. In this sense, the qualitative-quantitative category of mixed-methods was used. The Career Decision-Making Self-Efficacy Scale and course evaluation form were utilised to examine the effectiveness of this course, consisting of theory and practice for a total of 14 weeks. The experimental group includes of senior students from the Department of Counseling and Guidance who chose the course, while the control group includes of senior students who didn’t choose the course and were studying in the same department. Both groups were administered the Career Decision-Making Self-Efficacy Scale as pre-test and post-test, and in addition to this, an evaluation form was used for the experimental group as a post-test. When the results obtained from the quantitative data are examined, the experimental group made progress and there was a significant difference between the experimental group and the control group in terms of the total score for career decision-making self-efficacy levels and the subscales of career decision-making self-efficacy in terms of job/occupational information, career choice and ways of creating a career plan. The qualitative findings were grouped into three categories: change as a result of the course, limitations and strengths of the implementation.